Extension and Feasibility of the Woods Report to the Developing Countries - Hameed, Syed (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1971)
This paper attempts to evaluate the adequacy of the theoretical model used in the Woods Task Force Report, explores the possibility of Us extension to the analysis of the comparative industrial relations systems and examines the feasibility of exporting certain elements of the Canadian industrial relations system to the developing countries.